2018
DOI: 10.1016/j.psychres.2018.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a coherent and replicable measurement model of the Edinburgh Postnatal Depression Scale

Abstract: HighlightsStandard factor analytic methods were used to explore the measure structure.Using the same methods in a recent study with two groups of women it was possible to make direct comparisons between responses at key time points after birth.A three factor model of the EPDS fitted the data best with both data sets.The three factors identified could be used in screening practice and tested further in research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…One of our inclusion criteria was that the mother had an infant between 2 and 10 months and although the majority (83%) of the T2 assessments were conducted between 8 and 20 weeks postpartum, T2 assessments were conducted with a quite wide timeframe (Table 1). Recently, a paper by Martin and Redshaw reported that mothers, who did not differ on other background variables, scored significantly different on the EPDS at three and six months postpartum [43]. However, based on the current data, it is not possible to address the question of whether an EPDS-score obtained for example at two months postpartum is more or less likely to reflect an underlying depression than at a later time point in the postpartum period.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One of our inclusion criteria was that the mother had an infant between 2 and 10 months and although the majority (83%) of the T2 assessments were conducted between 8 and 20 weeks postpartum, T2 assessments were conducted with a quite wide timeframe (Table 1). Recently, a paper by Martin and Redshaw reported that mothers, who did not differ on other background variables, scored significantly different on the EPDS at three and six months postpartum [43]. However, based on the current data, it is not possible to address the question of whether an EPDS-score obtained for example at two months postpartum is more or less likely to reflect an underlying depression than at a later time point in the postpartum period.…”
Section: Discussionmentioning
confidence: 74%
“…More recently, a researchers have questioned the utility of continously conducting EFA as opposed to data and theory-driven confirmatory factor analyses (CFAs), (e.g. [40, 43]) and related to this, the optimal length of the EPDS has been questioned [44]. However, as there is currently no genereally agreed upon factor structure that could serve as the basis for a CFA, in the present study, we decided to assesss the factor structure of the EPDS using EFA.…”
Section: Introductionmentioning
confidence: 99%
“…CFA was conducted on the remaining 60% of the data using Weighted Least Squares Mean and Variance (WLSMV), which uses polychoric correlations and robust corrections to account for ordinal and non-normally distributed data (e.g., Lydsdottir et al, 2019, Albuquerque et al2017, Martin and Redshaw, 2018. As much of the previous literature has used MLE, we also performed CFA using this method, and are reporting the results in the…”
Section: Cfamentioning
confidence: 99%
“…We considered it was essential to report the frequency of responses per each individual EPDS item, as recent studies have highlighted the need for this information (Martin 2018) in order to better understand the distributional characteristics of EPDS items…”
Section: Frequency Of Responses Per Each Individual Item Of the Epdsmentioning
confidence: 99%
See 1 more Smart Citation